Eletrodos impressos descartáveis e de carbono vítreo modificados com grafeno e compósito de nanotubos de carbono-quitosana aplicados na determinação de corantes de cabelo - Hudari, Felipe Fantinato [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Due to the use of dyes hair and the your high dilution in wastewater and water treatment plants after incomplete treatment, the demand for increasingly sensitive and robust analytical methods for its quantification is highly relevant. Thus, the present work describes the construction of two sensors for quantification of hair dyes. The first was the development of a glassy carbon electrode modified with composite MWCNTs-CHT for simultaneous determination of PPD and RSN in samples of commercial hair dye and in samples of tap water. The Ipa of RSN and PPD presented 60% and 100% increase, respectively, in modified electrode compared to the electrode without modification. The reaction between both was monitored by spectrophotometry in the region UV-Vis, mass spectrometry and electrochemical oxidation where it was possible to diagnose the formation of the Bandrowski base and other related products the hair coloring. An analytical curve for PPD and RSN was constructed and finding a linear range in the interval of 0.55 to 21.2 mg L-1 with detection limit of 0.79 and 0.58 mg L-1, respectively. The method was applied to samples of tap water with recovery around 100% and in sample of commercial hair dye (EMBELLEZE MAXTON? (2.0 preto natural)), finding 24.10 and 10.34 mg g-1 of dye for PPD and RSN, respectively. The method was valeted by spectrophotometry. Other electroanalytical method was developed using screen printed electrode modified with grapheme for determining of the temporary dye BA-41 in 0,1 mol L-1 of B-R buffer pH 6,90. The peak current is 1,300% greater when compared with screen printed and glassy carbon electrodes, both unmodified. Through the technique of square wave voltammetry, the method was optimized of multivariate form using factorial design 24 and Doehlert matrix. Under optimized conditions of f (67 Hz), pH (6,90), ?E (128 mV) and Esw (6 mV), we constructed a calibration curve with a...
Keywords: Quimica analitica; Eletrodo de carbono; Corantes; Nanotubos de carbono; Grafeno; Dyes